Essentials of Nursing Law and Ethics - Westrick, Susan J. (Jones and Bartlett Publishers, 2009)
Keywords: Law and legislation; Nursing ethics; Nursing; United States; dept.nur; faculty_collection

Evidence-Based Nursing Guide to Legal & Professional Issues. - Westrick, Susan J.; Lippincott Williams & Wilkins (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
Keywords: Law and legislation; Nursing; United States; dept.nur; faculty_collection

The Pediatric Nurse's Survival Guide - Rebeschi, Lisa M.; Brown, Mary H. (Thomson Delmar Learning, 2007)
Keywords: Handbooks, manuals, etc; Pediatric nursing; dept.nur; faculty_collection

Legal and Ethical Issues - Westrick, Susan J.; Dempski, Katherine (Quick look nursing, 2006)
Keywords: Law and legislation; Nursing ethics; Nursing; dept.nur; faculty_collection

Pathophysiology - Crutchlow, Eileen M. (Quick look nursing, 2002)
Keywords: Physiology, Pathological; Nursing; dept.nur; faculty_collection

The Pediatric Nurse's Survival Guide - Rebeschi, Lisa M. (Delmar, 2002)
Keywords: Handbooks, manuals, etc; Pediatric nursing; dept.nur; faculty_collection

Legal and Ethical Issues - Westrick, Susan J.; Dempski, Katherine (Quick look nursing, 2000)
Keywords: Law and legislation; Nursing ethics; Nursing; dept.nur; faculty_collection

Counselors’ conceptualizations of caring in the counseling relationship - Halstead, R.W.; Wagner, L.D.; Vivero, M.; Ferkol, W. (Counseling and Values, 2002)
Caring is a concept that has been studied in numerous helping professions but has yet to be researched from a counseling perspective. In this qualitative research study, 13 master’s-level counseling interns were interviewed to better understand their perceptions of caring in the counseling relationship. Results suggest that these interns perceive that supporting desired outcomes, a personal capacity for caring, maintaining therapeutic conditions, mutuality in the counseling relationship, and a dynamic flow of communication are important attributes of the counseling relationship when caring is present The findings suggest further research that explores the concept of caring in the counseling relationship may be warranted. © 2002 American Counseling Association.
Keywords: dept.nur

Care of the Laparoscopic Nissen Fundoplication Patient - Aronson, B.S.; Yeakel, S.; Ferrer, M.; Caffrey, E.; Quaggin, C. (Gastroenterology Nursing, 2001)
Gastroesophageal reflux disease can usually be successfully managed with conservative medical treatment. Anti-reflux surgery is a safe alternative when treatment fails or patients desire a more definitive treatment option. Through a case study approach, this article describes the indications for surgery, the essentials of the authors’ multi-disciplinary approach to care and the components of a well-designed education plan for a patient undergoing laparoscopic Nissen fundoplication. Although most patients do well after surgery, diligent nursing care is required before and after surgery to prevent or manage complications and ensure patients have a rapid recovery and successful outcome. © 2001 Lippincott Williams & Wilkins, Inc.
Keywords: Fundoplication; Gastroesophageal Reflux; Gastroscopy; Humans; Male; Middle Aged; Patient Care Team; Patient Discharge; Patient Education; Patient Selection; Perioperative Care; Treatment Outcome; case report; dept.nur; gastroesophageal reflux; gastroscopy; hospital discharge; human; male; methodology; middle aged; nursing; organization and management; patient care; patient education; patient selection; perioperative period; review; stomach fundoplication; treatment outcome

Pain in older adults - Wallace, M. (Annals of Long-Term Care, 2001)
Pain is a prevailing clinical problem among older adults resulting in systemic agitation and altered quality of life. Although the possibility remains that older adults experience and report less pain, the need exists to objectively evaluate pain in order to provide the most effective pain management. Several standardized tools are available to assess pain in older adults at baseline and at subsequent, frequent intervals. Following an objective assessment, pain may be managed with pharmacologic and nonpharmacologic methods.
Keywords: Alzheimer disease; acetylsalicylic acid; aged; amitriptyline; analgesic agent; anticonvulsive agent; carbamazepine; choline magnesium trisalicylate; clonazepam; codeine; corticosteroid; dementia; dept.nur; desipramine; dose response; doxepin; drug effect; drug formulation; drug indication; fentanyl; gabapentin; human; hydrocodone; hydromorphone; ibuprofen; imipramine; intravenous anesthetic agent; local anesthetic agent; morphine sulfate; naproxen; narcotic analgesic agent; nonsteroid antiinflammatory agent; nortriptyline; opiate; oxycodone; pain; pain assessment; paracetamol; prednisone; review; side effect; tricyclic antidepressant agent; unindexed drug; visual analog scale; ⛔ No DOI found

Moving forward together: The practice doctorate in nursing - O'Sullivan, A.L.; Carter, M.; Marion, L.; Pohl, J.M.; Werner, K.E. (Online Journal of Issues in Nursing, 2005)
Societal drivers, as well as trends in education and health care, are advancing the practice doctorate in nursing. For nurse practitioner preparation, the current resurgence of interest in the practice doctorate could precipitate change that mimics the evolution from post-basic certificate to Master's level education. The National Organization of Nurse Practitioner Faculties (NONPF) is a resource for the study of the practice doctorate relative to quality nurse practitioner education. This article will offer some insights into the movement toward the practice doctorate by describing, from the NP perspective, the societal impetus for change, the historical perspective of NP and doctoral education, the 4 Ws (why, what, where, and when) of the movement, and some of the myths and realities about the practice doctorate. © 2005 Online Journal of Issues in Nursing.
Keywords: NONPF; Nurse practitioner; Nursing education; Practice doctorate; cultural anthropology; demography; dept.nur; education program; evolution; health care; health care organization; health care quality; health care system; health practitioner; medical education; medical practice; nursing; review; ⛔ No DOI found

Carelink: Partners in a caring Model: A cardiac management program for home care - Shellman, J.; Lacey, K.; Clemmens, D. (Home Healthcare Nurse, 2008)
As a model of care, CARELINK promotes self-care and self-management of chronic illnesses for homebound older adults no longer eligible for skilled nursing services. A case-study method is used to highlight the key constructs and outcomes related to the model. The benefits of applying the CARELINK model as a cardiac management program for home care are discussed.
Keywords: Aged; Chronic Disease; Education, Nursing; Empathy; Geriatric Nursing; Heart Diseases; Home Care Services; Humans; Male; Models, Nursing; Self Care; aged; article; chronic disease; dept.nur; education; empathy; geriatric nursing; heart disease; home care; human; male; methodology; model; nursing; nursing education; organization and management; self care

Strategies for enhancing student learning by managing ambiguities in clinical settings. - Taylor, P.A. (Nurse educator, 2000)
Have you ever watched as care providers, be they student nurses or staff nurses, display behaviors that seem to indicate that they are becoming overwhelmed by situations in the acute care setting? Have you also observed other providers who seem to thrive on the "challenges" presented by these same situations? The same situation stimulates responses that reflect opposite ends of a continuum, the continuum of tolerance of ambiguity. The nurse educator needs to develop a greater understanding of the elements in the clinical situation (the ambiguities) that have stimulated the behavioral responses, and how an individual's level of tolerance of ambiguity influences reactions to the ambiguous situations. These understandings provide the nurse educator with the foundation for developing teaching strategies to facilitate effective management of ambiguous situations in clinical settings.
Keywords: *Burnout, Professional/pc [Prevention & Control]; *Education, Nursing/mt [Methods]; *Nurses/px [Psychology]; *Teaching/mt [Methods]; Burnout, Professional; Education, Nursing; Humans; Nurses; Nursing Process; Teaching; article; burnout; dept.nur; human; methodology; nurse; nursing education; nursing process; psychological aspect; teaching

Care of the adult patient with cystic fibrosis. - Aronson, Barbara S; Marquis, Melissa (Medsurg nursing : official journal of the Academy of Medical-Surgical Nurses, 2004)
Recently published consensus statements and conference proceedings from the Cystic Fibrosis Foundation provide new direction with regard to the etiology, diagnosis, and treatment of the adult patient with cystic fibrosis (CF). Survival has improved through early diagnosis and improved treatment, and aggressive management of complications. The current state of knowledge, the most recent evidence-based treatment options, and essentials of nursing care for the adult patient with CF are outlined.
Keywords: *Cystic Fibrosis/th [Therapy]; Adult; Age Factors; Cystic Fibrosis; Cystic Fibrosis/di [Diagnosis]; Cystic Fibrosis/ep [Epidemiology]; Cystic Fibrosis/et [Etiology]; Diabetes Mellitus; Diabetes Mellitus/et [Etiology]; Diabetes Mellitus/pc [Prevention & Control]; Female; Gastrointestinal Diseases; Gastrointestinal Diseases/et [Etiology]; Gastrointestinal Diseases/pc [Prevention & Control]; Genetic Predisposition to Disease; Genetic Predisposition to Disease/ge [Genetics]; Humans; Infection Control; Infection Control/mt [Methods]; Longevity; Nurse's Role; Phenotype; Reproductive Medicine; Reproductive Medicine/mt [Methods]; Respiratory Therapy; Respiratory Therapy/mt [Methods]; Respiratory Tract Infections; Respiratory Tract Infections/et [Etiology]; Respiratory Tract Infections/pc [Prevention & Control]; Terminal Care; Terminal Care/mt [Methods]; adult; age; artificial ventilation; case report; cystic fibrosis; dept.nur; diabetes mellitus; female; gastrointestinal disease; genetic predisposition; genetics; human; infection control; longevity; methodology; nurse attitude; phenotype; reproduction; respiratory tract infection; review; terminal care; ⛔ No DOI found

Too toxic - Saccomano, Scott; Deluca, Deborah A (Nursing management, 2008)
Firm up on the facts and considerations associated with acetaminophen toxicity.
Keywords: *Acetaminophen/po [Poisoning]; *Analgesics, Non-Narcotic/po [Poisoning]; *Liver Failure, Acute/ci [Chemically Induced]; Acetaminophen; Acetaminophen/pk [Pharmacokinetics]; Analgesics, Non-Narcotic; Analgesics, Non-Narcotic/pk [Pharmacokinetics]; Antidotes; Drug Overdose/nu [Nursing]; Drug Overdose/pp [Physiopathology]; Drug Overdose/th [Therapy]; Humans; Liver Failure, Acute; Liver Failure, Acute/nu [Nursing]; Liver Failure, Acute/pp [Physiopathology]; Liver Failure, Acute/th [Therapy]; Overdose; Patient Education as Topic; Sorption Detoxification; Sorption Detoxification/mt [Methods]; analgesic agent; antidote; chemically induced disorder; dept.nur; detoxification; human; intoxication; liver failure; methodology; nursing; paracetamol; pathophysiology; patient education; peer-reviewed; review

Enhancing evidence bases for interventions in a baccalaureate program. - Aronson, Barbara S; Rebeschi, Lisa M; Killion, Susan Westrick (Nursing education perspectives, 2007)
Modifying the sequence, objectives, and research-based content for a nursing interventions course in a baccalaureate curriculum resulted in improved outcomes including enhancement of the evidence bases for nursing interventions. A mixed methods research study demonstrated better student preparation for clinical experiences and improved satisfaction with course content, consistency, and sequencing. Faculty reported improved integration of theory, research, and practice. Although grades were slightly lower in the new course, the positive outcomes greatly outweighed this expected finding. A foundation for improving the evidence bases for future nursing practice is guided by the curricular modifications described in this article.
Keywords: *Attitude of Health Personnel; *Curriculum; *Education, Nursing, Baccalaureate/og [Organization & Administration]; *Evidence-Based Medicine/ed [Education]; *Nursing Research/ed [Education]; *Students, Nursing/px [Psychology]; Attitude of Health Personnel; Clinical Competence; Connecticut; Curricular and course development; Curriculum; Curriculum/st [Standards]; Diffusion of Innovation; Education, Nursing, Baccalaureate; Evidence-Based Medicine; Evidence-based interventions; Faculty, Nursing; Focus Groups; Health Knowledge, Attitudes, Practice; Health Services Needs and Demand; Humans; Nursing Education Research; Nursing Methodology Research; Nursing Research; Organizational Objectives; Program Evaluation; Qualitative Research; Questionnaires; Skills laboratory; Student learning outcomes; Students, Nursing; Surveys and Questionnaires; United States; article; attitude to health; clinical competence; curriculum; dept.nur; education; evaluation; evidence based medicine; health care quality; health personnel attitude; health service; human; information processing; mass communication; nursing education; nursing methodology research; nursing research; nursing student; organization; organization and management; peer-reviewed; psychological aspect; qualitative research; questionnaire; standard; ⛔ No DOI found

Registered nurses and delegation. - Saccomano, Scott J (The Pennsylvania nurse, 2007)
Keywords: *Delegation, Professional/og [Organization & Administration]; *Nursing Assistants/og [Organization & Administration]; *Nursing Staff/og [Organization & Administration]; *Nursing, Supervisory/og [Organization & Administration]; American Nurses' Association; Clinical Competence; Delegation, Professional; Humans; Licensure, Nursing; Nurse's Role; Nurses' Aides; Nursing Assistants/ed [Education]; Nursing Staff; Nursing, Supervisory; Practice Guidelines; Practice Guidelines as Topic; Professional Autonomy; United States; clinical competence; dept.nur; education; human; licensing; medical society; nurse attitude; nursing; nursing assistant; nursing staff; organization and management; practice guideline; professional delegation; professional practice; review; ⛔ No DOI found

Assessment of nursing student's learning outcomes and employment choice after the implementation of a senior capstone course. - Rebeschi, Lisa; Aronson, Barbara (International journal of nursing education scholarship, 2009)
Many undergraduate baccalaureate nursing programs incorporate clinical emersion courses at the end of the program. Nursing capstone courses have become increasingly important in facilitating student transition into practice. However, little is known regarding the overall effectiveness of this teaching model for students, nursing programs, and clinical agencies. Previous studies revealed conflicting results about the benefits of a senior level precepted clinical experience. In this multi-method study, the authors examined student learning outcomes, perceptions, employment choice and retention following implementation of a new capstone nursing course. Results of this study indicated that a capstone course does not necessarily significantly improve scores on achievement exams or NCLEX RN first time pass rates. Nevertheless, qualitative content analysis revealed the following themes: integration, autonomy, confidence, authority, and advocacy consistent with a perceived enhanced competence in the nursing role. Data indicated that graduates often seek employment and remain at their capstone site or within their capstone specialty.
Keywords: *Attitude of Health Personnel; *Choice Behavior; *Clinical Competence; *Education, Nursing, Baccalaureate/og [Organization & Administration]; *Employment/px [Psychology]; *Students, Nursing/px [Psychology]; Adult; Attitude of Health Personnel; Capstone; Choice Behavior; Clinical Competence; Clinical Competence/st [Standards]; Clinical teaching; Education, Nursing, Baccalaureate; Employment; Female; Humans; Licensure, Nursing; Male; Middle Aged; Models, Educational; Models, Nursing; New England; Nurse's Role; Nurse's Role/px [Psychology]; Nursing Education Research; Nursing Methodology Research; Nursing education; Personnel Turnover; Personnel Turnover/sn [Statistics & Numerical Data]; Preceptorship; Preceptorship/og [Organization & Administration]; Professional Autonomy; Program Development; Program Evaluation; Qualitative Research; Self Efficacy; Students, Nursing; United States; Use of preceptors; adult; article; clinical competence; decision making; dept.nur; education; educational model; employment; evaluation; female; health care quality; health personnel attitude; human; licensing; male; middle aged; model; nurse attitude; nursing education; nursing methodology research; nursing student; organization and management; personnel management; professional practice; program development; psychological aspect; qualitative research; self concept; standard; statistics

Family rituals that provide meaning for single-parent families: - Moriarty, Patricia Hale; Wagner, Linda D (Journal of Family Nursing, 2004)
The number of single-parent families has increased dramatically in the United States. The purpose of this study was to explore the types of family rituals present in single-parent families and their meaning within the family context. Little is known about family rituals in single-parent families, and therefore grounded theory was the qualitative research method used for this study. Unstructured face-to-face interviews were used to obtain data from a theoretical sample of seven single parents. Data analysis appropriate to the grounded theory method was utilized to identify a core variable and an emerging theory. Six types of rituals: connection, spiritual, love, recreation, celebration, and evolving were found to be used by these single-parent families as a way to facilitate family cohesion and instill family values. Applicability of the findings of this study are beneficial for nurses working with clients with diverse, changing, and complex social situations such as the single-parent family. © 2004 Sage Publications.
Keywords: Family health; Qualitative research; Rituals; Single-parent family; dept.nur

Adolescent attitudes, beliefs, and concerns regarding breastfeeding. - Nelson, Antonia M (MCN. The American journal of maternal child nursing, 2009)
Purpose: To investigate the attitudes, beliefs, and concerns of pregnant and postpartum adolescents regarding breastfeeding. Study Design and Methods: Audiotaped focus groups of low-income, largely minority pregnant and postpartum adolescents were conducted and transcripts analyzed using content analysis techniques. Findings: Major themes identified were in the area of beliefs, such as They say it's healthy, or It hurts; attitudes, such as breastfeeding is the mother's choice and The baby comes first; and concerns such as privacy, and Breastfeeding leads to dependency. Clinical Implications: Adolescents can be encouraged to breastfeed, but require appropriate education beyond what they have heard from others. Myths such as pain during breastfeeding need to be addressed. Since teens want to learn but not be told what to do, active learning strategies such as guided Internet searches could be helpful to guide them into discovery of the benefits of breastfeeding. Since all the teens in this study felt that the baby comes first, emphasizing the benefits of breastfeeding for the baby should predominate educational efforts. Concerns related to physical exposure while breastfeeding can be addressed antenatally through discussing creative strategies to maintain modesty. This study suggests that, in the postpartum hospital setting, adopting a sensitive, initially hands-off' approach to supporting breastfeeding might be more well-accepted than tactile assistance, and that following the initial establishment of a milk supply, various levels of breastfeeding exclusivity should be considered as potentially acceptable infant feeding patterns.
Keywords: *Breast Feeding/px [Psychology]; *Health Knowledge, Attitudes, Practice; *Mothers/ed [Education]; *Mothers/px [Psychology]; *Psychology, Adolescent; Adolescent; Adolescent Psychology; Breast Feeding; Breastfeeding; Female; Focus Groups; Focus groups; Health Knowledge, Attitudes, Practice; Health Promotion; Humans; Mothers; Postpartum Period; Postpartum Period/px [Psychology]; Pregnancy; Qualitative research; Young Adult; adolescent; adult; article; attitude to health; breast feeding; child psychology; dept.nur; education; female; health promotion; human; information processing; mother; pregnancy; psychological aspect; puerperium

Antibiotic-taking experiences of undergraduate college students. - Aronson, Barbara S (Journal of the American Academy of Nurse Practitioners, 2006)
Purpose: The purpose of this qualitative descriptive study was to explore the medication-taking experiences of undergraduate college students prescribed short-term antibiotic therapies and to describe factors influencing their adherence. Data sources: Thirty-four undergraduate students prescribed antibiotics for treatment of an acute infectious illness at a large university health center were recruited to participate in this study. Semistructured telephone interviews were conducted after students finished their course of treatment. Qualitative descriptive content analysis was used to analyze the transcripts typed from the audio-taped phone interviews. Conclusions: The main theme that emerged from the data was antibiotic-taking self-management. Most participants were able to adapt medication regimens into their daily routines, and used events in their day and specific reminder strategies to help them to remember to take their medications. This occurred despite an ever-changing class and work schedule and being prescribed complex, lengthy antibiotic regimens. Most dosing errors occurred during times when schedules changed or students were off campus during weekends or college breaks. A small number of students discontinued therapy early because of side effects or forgetfulness. Implications for practice: By understanding factors that influence antibiotic adherence from a college student perspective, healthcare providers can suggest strategies to promote adherence that are tailored to the specific needs of this unique population. © 2006 American Academy of Nurse Practitioners.
Keywords: *Anti-Bacterial Agents/tu [Therapeutic Use]; *Patient Compliance; *Self Care; *Students; Adolescent; Adult; Anti-Bacterial Agents; Antibiotic adherence; College students; Female; Humans; Male; Medication self-management; Patient Compliance; Self Care; Students; United States; adolescent; adult; antiinfective agent; article; dept.nur; female; human; male; patient compliance; self care; student